Organizational Climate: Characterization from the Perspective of Senati Students - Perú - Espinoza Palomino, Segundo Antonio; Silva Juárez, Raquel; Seminario-Morales, María-Verónica; Villalta Arellano, Segundo Ramos; Arévalo Rodríguez, Mirian Elizabeth; Lujan-Vera, Priscila E. (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The organizational climate is the work environment conceived by emotions and motivation of an organization and, an optimal way of increasing participation is with working groups in the dependencies to improve: objectives, processes, conflicts, leadership. Thus the objective was to determine the characterization of variables. The method incorporates the quantitative approach, non -experimental design, descriptive level, applied and transversal type, analysis and deductive methods. The results show, there is a high organizational climate level, due to the contribution of three dimensions or aspects that are: economic conditions, management values and organizational policies.